Succession planning in family farm businesses - Scott-Ladd, Brenda; Noonan, J. (Forum Manajemen Indonesia, 2012)
Succession planning is a challenge for any business and this is particularly the case for small and or family businesses. Implementing succession planning requires that a holistic and long-term approach is taken and relies on having a viable business that has worth to the successor. This paper reports on an action research study that evaluates the progress of a multidisciplinary and multilevel facilitated resilience program to improve farm sustainability over the longer term. A team of facilitators from various discipline backgrounds worked with farmers in a series of workshops to develop strategic plans encompassing financial, work, personal and farm management goals, along with succession planning, to assist improve the resilience of these businesses. Data were gathered from the facilitators and participants at the end of each workshop, and this data was collated with their feedback to an internet blog and with additional feedback sessions. The outcome indicates that the multidisciplinary approach encouraged sharing of ideas and information and assisted participants in developing and formalising their planning processes. Insights in this paper include the difficulties and challenges of succession planning and the role of multi-disciplinary facilitation teams to gain engagement and confidence in the planning process.